Effect of Gamma Radiation and Curcuma xanthorrhiza Extract Capsules on Damage Mus musculus Liver Cells: Efek Radiasi Gamma dan Kapsul Ekstrak Temulawak (Curcuma xanthorrhiza) terhadap Kerusakan Sel Hepar Mencit (Mus musculus) - Septiana Kurniasari; Fatimah K Hentihu (Akademi Farmasi Surabaya, 2022)
Gamma radiation produces free radicals when interacting with cells. The free radical can be neutralized and caught by an antioxidant compound. This research aimed to analyze the effect of gamma radiation exposure and treated Curcuma xanthorrhiza extract capsules on the cells damage to the mice’s liver. This study used mice of the Balb/c strain with an average body weight of 18-20 grams, aged 6-8 weeks and male. This study required 80 animals for 3 groups, namely K- (without radiation and extract), R- (gamma radiation without extract of Curcuma xanthorrhiza) and R+ (given extract and then irradiated). Radiation exposure was given for 10 minutes, 20 minutes, 30 minutes, 40 minutes and 50 minutes, while Curcuma xanthorrhiza extract was given in 5 different doses, namely, 1.4 g/kg body weight; 2.0 g/kg body weight; 2.6 g/kg body weight; 3.2 g/kg body weight and 3.8 g/kg body weight. The damaging of liver cells is done by analyzing its microscopic picture. The result showed increased exposure time to gamma radiation causes increased cell damage. Cell damage is low in a row of increasing Curcuma xanthorrhiza extract dose. The adequate amount of Curcuma xanthorrhiza extract is 3.8 g/kg body weight.